(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Zirconium oxide (ZrO2), is a versatile material with exceptional properties, making it valuable in various fields. This research focuses on the synthesis of ZrO2 nanoparticles through a chemical method and explores the influence of synthesis parameters. The Sol-Gel method was employed, and structural and morphological characterizations were performed. X-ray diffraction analysis revealed crystalline properties, with an average crystallite size of 13.21 nm. Field Emission Scanning Electron Microscopy (FE-SEM) showed spherical particles with an average size of 14 nm. FTIR spectroscopy confirmed the formation of ZrO2. This study enhances our understanding of ZrO2 nanoparticles and their potential applications